THE IMPACT OF ROUTING OPTION ON TANGERANG BUS LANE CORRIDOR - Alvinsyah Alvinsyah; Udayalaksmanakartiyasa Halim (Jurnal Transportasi, 2012)
The objective of this study is to analyze the impact of re-routing bus lane corridor on some performance indicators. The Tangerang Bus Lane is taken as a case study. The discussion is focused on comparison of service planning performance indicators such ridership, passenger-km, and bus-km. A primary survey on bus operational characteristics and user attitude is conducted. Prior to the analysis, some basic formula is derivedand modified and, then, performance indicators for both route option are estimated. The analysis is conducted by comparing the estimated indicators. The result shows that the alternative route gives better performance and yields to a need of re-evaluating the originally proposed route.Keywords: Bus lane, performance indicator, ridership, service productivity